2023
DOI: 10.3390/ijms24065540
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipase A2 and Interleukin-6 Levels as Predictive Markers of the Severity and Outcome of Patients with COVID-19 Infections

Abstract: Coronavirus disease (COVID-19) has become a global pandemic. COVID-19 patients need immediate diagnosis and rehabilitation, which makes it urgent to identify new protein markers for a prognosis of the severity and outcome of the disease. The aim of this study was to analyze the levels of interleukin-6 (IL-6) and secretory phospholipase (sPLA2) in the blood of patients regarding the severity and outcome of COVID-19 infection. The study included clinical and biochemical data obtained from 158 patients with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…PLB1 phospholipase cleaves both sn-1 and sn-2 acyl chains and is active in human neutrophils, suggesting a role in the generation of lipid mediators of inflammation [106]. Furthermore, secretory phospholipase A2, which cleaves only the sn-2 acyl chain, is a predictive marker of the severity and outcome of COVID-19 patients [172]. GRB14 is a negative regulator of the insulin receptor [117].…”
Section: Genes/proteins Indirectly Related To Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…PLB1 phospholipase cleaves both sn-1 and sn-2 acyl chains and is active in human neutrophils, suggesting a role in the generation of lipid mediators of inflammation [106]. Furthermore, secretory phospholipase A2, which cleaves only the sn-2 acyl chain, is a predictive marker of the severity and outcome of COVID-19 patients [172]. GRB14 is a negative regulator of the insulin receptor [117].…”
Section: Genes/proteins Indirectly Related To Covid-19mentioning
confidence: 99%
“…However, USP24 promotion in M2 macrophages increases IL-6 transcription by stabilizing p300 and β-TrCP [164]. Increased IL-6 is a biomarker in COVID-19 [172]. Promoted LSAMP can induce the expression of the hippocampal mineralocorticoid receptor (MR) [50], and MR stimulation also promotes IL-6 expression [51].…”
Section: Immune Responses and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Stanislav Urazov et al from Russia and Israel [23] analyzed the levels of interleukin-6 (IL-6) and secretory phospholipase (sPLA2) in the blood samples of patients in relation to the severity and outcome of COVID-19. They showed that the levels of both IL-6 and sPLA2 could be early predictors of aggravation of COVID-19.…”
mentioning
confidence: 99%